Microfluidics for Cells and Other Organisms - van Noort, Danny (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Microfluidics-based devices play an important role in creating realistic microenvironments in which cell cultures can thrive. They can, for example, be used to monitor drug toxicity and perform medical diagnostics, and be in a static-, perfusion- or droplet-based device. They can also be used to study cell-cell, cell-matrix or cell-surface interactions. Cells can be either single cells, 3D cell cultures or co-cultures. Other organisms could include bacteria, zebra fish embryo, C. elegans, to name a few.
English
Keywords: n/a; screening; microfluidic device; cell homogenous dispersion structure; RNA; biomedical engineering; neural networks; single-cell mechanics; on-chip cell incubator; cell growth; embryogenesis; cancer stem cell; intracellular proteins; simultaneous multiple chamber observation; instrumentation; fnRBC; cancer metastasis; Wheatstone bridge; capillary; single-cell manipulation; adherent cells; nucleic acid; micropipette aspiration; sample preparation; unsupervised learning; cell motility; capture efficiency; bacterial concentration; cbNIPD; microfabrication; drug resistance; variational inference; microfluidics; periodic hydrostatic pressure; paracrine signaling; periodic pressure; capacitively coupled contactless conductivity detection (C4D); bioMEMS; microfluidic flow cytometry; particle/cell imaging; co-culture; cells-in-gels-in-paper; laminar flows; E. coli; printed-circuit-board (PCB); pneumatic microvalve; time-lapse observation; nanostructure; 3D particle focusing; target cell-specific binding molecules; absolute quantification; DNA; zebrafish embryo; microscopy; 3D printing; 3D flow focusing; single-cell analysis